Enhancement of transdermal absorption, gene expression and stability of tyrosinase plasmid (pMEL34)-loaded elastic cationic niosomes: Potential application in vitiligo treatment - Jiradej Manosroi (2018)
The pMEL34 was loaded in elastic cationic niosomes (Tween61/Cholesterol/ DDAB at 1:1:0.5 molar ratio) by chloroform film method with sonication and rehydrated with 25% ethanol. The amount of pMEL34 was determined by gel electrophoresis and gel documentation. The maximum loading of pMEL34 in elastic cationic niosomes was 150 mg/16mg of the niosomal compositions. At 8 weeks, the remaining plasmid in the elastic niosomes kept at 4±2°C, 27±2°C were 49.75% and 38.57%, respectively, whereas at 45±2°C, all plasmids were degraded. For transdermal absorption through rat skin investigated by Franz diffusion cells at 6 h, the fluxes of pMEL34 loaded in elastic and nonelastic niosomes in viable epidermis and dermis (VED) were 0.022±0.00 and 0.017±0.01 μg/cm2/h, respectively, whereas only pMEL34 loaded in elastic cationic noisome was observed in the receiver solution. The pMEL34 loaded in elastic cationic niosomes showed the highest tyrosinase gene expression demonstrating higher tyrosinase activity than the free and the loaded plasmid in nonelastic niosomes of about four times. This study has suggested the potential application of elastic cationic niosomes as an efficient topical delivery for tyrosinase gene in vitiligo therapy. © 2010 Wiley-Liss, Inc. and the American Pharmacists Association.